Sleepiness and accidents among professional drivers - Halvani, Gholam Hossein (Array, 2019)
The aim of this study was to investigate the relation between sleepiness and accidents among professional drivers in Iran. This is a case-control study carried out among 820 professional drivers of whom 300 drivers were assigned to the case group and 520 drivers were as the control group, of whom 104 cases were excluded from the study because their questionnaire was not completed. Finally, the collected data on 716 cases were analyzed. The data relating to road traffic accidents, demographic factors and sleepiness were collected using questionnaire and interview. Data analysis was performed using SPSS16 (Statistical Package for the Social Sciences version 16). The mean of sleepiness score among cases was 6.2 whereas this mean in control group was 4.6. 20.9% of the experimental group had Epworth Sleepiness Scale (ESS)>10 while just 8.2% of the controls had ESS>10.